2004
DOI: 10.1111/j.1469-0691.2004.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus mononucleosis as a cause of prolonged fever and prominent weight loss in immunocompetent adults

Abstract: Four immunocompetent adults presented with protracted fever lasting > 6 weeks and severe weight loss, associated with primary cytomegalovirus (CMV) infection. Each patient had spleen enlargement, lymphocytosis and hypertriglyceridaemia, but recovered spontaneously. A further 20 immunocompetent patients with primary CMV infection were also reviewed, and all presented the usual clinical picture of CMV mononucleosis. It was concluded that CMV mononucleosis should be considered in the differential diagnosis in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The increased availability of serology-biomolecular assays, which support a prompt recognition and monitoring of acute-relapsing cytomegalovirus infection which may complicate immunodeficiency [4,6,7,13,14], have allowed physicians to add these assays to the workup of FUO. As a result, an apparent rise of these diagnoses during unexplained viral diseases or FUO have been observed [11,18,20], and also studies performed in sexually transmitted disease clinics confirmed this tendency [21,22]. Eighty-one cases of primary cytomegalovirus infection in immunocompetent hosts were retrospectively reviewed [18], but laboratory examinations did not remain consistent during the 10-year period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The increased availability of serology-biomolecular assays, which support a prompt recognition and monitoring of acute-relapsing cytomegalovirus infection which may complicate immunodeficiency [4,6,7,13,14], have allowed physicians to add these assays to the workup of FUO. As a result, an apparent rise of these diagnoses during unexplained viral diseases or FUO have been observed [11,18,20], and also studies performed in sexually transmitted disease clinics confirmed this tendency [21,22]. Eighty-one cases of primary cytomegalovirus infection in immunocompetent hosts were retrospectively reviewed [18], but laboratory examinations did not remain consistent during the 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of mononucleosis-like syndrome and organ involvement by primary cytomegalovirus infection tested lower in frequency, when compared with other experiences [16] and our survey. From Spain, four immunocompetent adults were described with primary cytomegalovirus disease expressing with fever lasting over 6 weeks, a mononucleosis-like syndrome, weight loss, and lymphocytosis [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fever for unknown reasons was shown in 12% of symptomatic HCMV infected neonates. Fever for unknown reasons may indicate the prenatal HCMV infection among neonates in this study since it presents the usual clinical picture of HCMV mononucleosis among immunocompetent children (42) . Heart diseases and feeding difficulties were last regarding the order of frequency.…”
Section: Discussionmentioning
confidence: 87%